Orange Pomace Improves Postprandial Glycemic Responses: An Acute, Randomized, Placebo-Controlled, Double-Blind, Crossover Trial in Overweight Men - Chen, C.-Y. Oliver (Nutrients, 2017)
Orange pomace (OP), a fiber-rich byproduct of juice production, has the potential for being formulated into a variety of food products. We hypothesized that OP would diminish postprandial glycemic responses to a high carbohydrate/fat breakfast and lunch. We conducted an acute, randomized, placebo-controlled, double blind, crossover trial with 34 overweight men who consumed either a 255 g placebo (PLA), a low (35% OP (LOP)), or a high (77% (HOP)) dose OP beverage with breakfast. Blood was collected at 0, 10, 20, 30, and 45 min and at 1, 1.5, 2, 3, 4, 5, 5.5, 6, 6.5, 7, and 8 h. Lunch was consumed after the 5.5-h blood draw. OP delayed the time (T(max)1) to the maximum concentration (C(max)1) of serum glucose during the 2-h period post breakfast by ≥36% from 33 (PLA) to 45 (HOP) and 47 (LOP) min (p = 0.055 and 0.013, respectively). OP decreased post-breakfast insulin C(max)1 by ≥10% and LOP delayed the T(max)1 by 14 min, compared to PLA at 46 min (p ≤ 0.05). HOP reduced the first 2-h insulin area under concentration time curve (AUC) by 23% compared to PLA. Thus, OP diminishes postprandial glycemic responses to a high carbohydrate/fat breakfast and the second meal in overweight men.